Promosi Dan Pemasaran Hasil Pertanian Skala Rumah Tangga Di Masa Pandemi Covid 19 - Awaluddin Hamzah; Iskandar Iskandar; Ilma Sarimustaqiyma Rianse; Salahuddin Salahuddin; Muhammad Aswar Limi (Jurnal Pengabdian Masyarakat Ilmu Terapan, 2022)
The Covid-19 pandemic has had an impact on various aspects of human life, including agriculture. Although affected, agricultural land can be a solution to the crisis. Food and economic security are very basic problems for households in the life of urban communities. The problem faced by the community in promoting and marketing household-scale agricultural products during the COVID-19 pandemic in Mokoau Village, Kambu District, Kendari City, is the lack of knowledge and skills in making promotional materials and marketing household-scale agricultural products by utilizing information technology and digital-based communication (internet); lack of knowledge and skills in implementing strategies for promotion and marketing of household-scale agricultural products by utilizing digital-based information and communication technology (internet). Based on the results of the implementation of this thematic KKN integrated community service activity, it can be concluded that the community can understand the importance of promoting digital-based horticultural agricultural products during the Covid-19 pandemic. The public is able to know and apply marketing techniques using internet media during the Covid-19 pandemic. The community is able to produce promotional video content for horticultural products and upload it on YouTube media. There is a new motivation from the community in utilizing unused land around settlements for horticultural farming development land. Community participation to take advantage of thematic KKN activities is still relatively low, due to various obstacles and their respective activities. People are increasingly aware of increasing their ability to take advantage of advances in information technology as an important medium for the success of marketing horticultural agricultural products.